Atraumatic trismus induced by duloxetine: an uncommon presentation of acute dystonia - Ohn, May Honey (BMJ Case Rep, 2021)
Atraumatic trismus can be one of the presentations of medication-induced acute dystonia, particularly by antipsychotics and less commonly antidepressants. A case of an unusual emergency presentation of atraumatic trismus on initiation of duloxetine is reported. The patient was a 40-year-old woman experiencing sudden difficulty in mouth opening and speaking due to a stiffened jaw after taking 5 days of duloxetine prescribed for her fibromyalgia-related chest pain. Assessment of vital signs is prudent to ensure there is no laryngeal involvement. Other physical examinations and her recent investigations were unremarkable. She was treated for acute dystonia and intravenous procyclidine was given together with oral diazepam. Her symptoms improved immediately and her duloxetine was suggested to be stopped. To our knowledge, this is the first case of isolated trismus induced by duloxetine. Clinicians should be aware of this risk, especially considering the limitation of important physiological functions (such as swallowing, eating, etc) associated with this condition.